Sugar and Salt: Bella Vista Chronicles # 4 : a novel - Wiggs, Susan (New York, NY : William Morrow, 2022)
"The New York Times bestselling author of The Lost and Found Bookstore returns to Perdita Street with a can't-miss tale of friendship, hardship, redemption, and love between a San Francisco baker and a barbecue master from Texas"--.
new book 2022 summer.
Keywords: Man-woman relationships; Family life; Women; Novels